Genome-wide characterization, expression analyses, and functional prediction of the NPF family in Brassica napus - Jing Wen (BMC Genomics, 2020)
Abstract Background NITRATE TRANSPORTER 1/PEPTIDE TRANSPORTER (NRT1/PTR) family (NPF) members are essential transporters for many substrates in plants, including nitrate, hormones, peptides, and secondary metabolites. Here, we report the global characterization of NPF in the important oil crop Brassica napus, including that for phylogeny, gene/protein structures, duplications, and expression patterns. Results A total of 199 B. napus (BnaNPFs) NPF-coding genes were identified. Phylogenetic analyses categorized these genes into 11 subfamilies, including three new ones. Sequence feature analysis revealed that members of each subfamily contain conserved gene and protein structures. Many hormone−/abiotic stress-responsive cis-acting elements and transcription factor binding sites were identified in BnaNPF promoter regions. Chromosome distribution analysis indicated that BnaNPFs within a subfamily tend to cluster on one chromosome. Syntenic relationship analysis showed that allotetraploid creation by its ancestors (Brassica rapa and Brassica oleracea) (57.89%) and small-scale duplication events (39.85%) contributed to rapid BnaNPF expansion in B. napus. A genome-wide spatiotemporal expression survey showed that NPF genes of each Arabidopsis and B. napus subfamily have preferential expression patterns across developmental stages, most of them are expressed in a few organs. RNA-seq analysis showed that many BnaNPFs (32.66%) have wide exogenous hormone-inductive profiles, suggesting important hormone-mediated patterns in diverse bioprocesses. Homologs in a clade or branch within a given subfamily have conserved organ/spatiotemporal and hormone-inductive profiles, indicating functional conservation during evolution. qRT-PCR-based comparative expression analysis of the 12 BnaNPFs in the NPF2–1 subfamily between high- and low-glucosinolate (GLS) content B. napus varieties revealed that homologs of AtNPF2.9 (BnaNPF2.12, BnaNPF2.13, and BnaNPF2.14), AtNPF2.10 (BnaNPF2.19 and BnaNPF2.20), and AtNPF2.11 (BnaNPF2.26 and BnaNPF2.28) might be involved in GLS transport. qRT-PCR further confirmed the hormone-responsive expression profiles of these putative GLS transporter genes. Conclusion We identified 199 B. napus BnaNPFs; these were divided into 11 subfamilies. Allopolyploidy and small-scale duplication events contributed to the immense expansion of BnaNPFs in B. napus. The BnaNPFs had preferential expression patterns in different tissues/organs and wide hormone-induced expression profiles. Four BnaNPFs in the NPF2–1 subfamily may be involved in GLS transport. Our results provide an abundant gene resource for further functional analysis of BnaNPFs.